Essential amino acid enriched high-protein enteral nutrition modulates insulin-like growth factor-1 system function in a rat model of trauma-hemorrhagic shock. - Xianfeng Xia (Public Library of Science (PLoS), 2013)
Background Nutrition support for critically ill patients supplemented with additional modular protein may promote skeletal muscle protein anabolism in addition to counteracting acute nitrogen loss. The present study was designed to investigate whether the essential amino acid (EAA) enriched high-protein enteral nutrition (EN) modulates the insulin-like growth factor-1 (IGF-1) system and activates the mammalian target of rapamycin (mTOR) anabolic signaling pathway in a trauma-hemorrhagic shock (T-HS) rat model. Methodology/principal findings Male Sprague-Dawley rats (n = 90, 278.18 ± 0.94 g) were randomly assigned to 5 groups: (1) normal control, (2) pair-fed, (3) T-HS, (4) T-HS and standard EN, and (5) T-HS and EAA enriched high-protein EN. Six animals from each group were harvested on days 2, 4, and 6 for serum, gastrocnemius, soleus, and extensor digitorum longus sample collection. T-HS significantly reduced muscle mass. Nutrition support maintained muscle mass, especially the EAA enriched high-protein EN. Meanwhile, a pronounced derangement in IGF-1-IGFBPs axis as well as impaired mTOR transduction was observed in the T-HS group. Compared with animals receiving standard EN, those receiving EAA enriched high-protein EN presented 18% higher serum free IGF-1 levels following 3 days of nutrition support and 22% higher after 5 days. These changes were consistent with the concomitant elevation in serum insulin and reduction in corticosterone levels. In addition, phosphorylations of downstream anabolic signaling effectors - including protein kinase B, mTOR, and ribosomal protein S6 kinase1 - increased significantly in rats receiving EAA enriched high-protein EN. Conclusion/significance Our findings firstly demonstrate the beneficial effect of EAA enriched high-protein EN on the metabolic modulation of skeletal muscle protein anabolism by regulating the IGF-1 system and downstream anabolic signaling transduction.